2007
DOI: 10.1103/physrevlett.98.153004
|View full text |Cite
|
Sign up to set email alerts
|

Solving the Kadanoff-Baym Equations for Inhomogeneous Systems: Application to Atoms and Molecules

Abstract: We implement time propagation of the nonequilibrium Green function for atoms and molecules by solving the Kadanoff-Baym equations within a conserving self-energy approximation. We here demonstrate the usefulness of time propagation for calculating spectral functions and for describing the correlated electron dynamics in a nonperturbative electric field. We also demonstrate the use of time propagation as a method for calculating charge-neutral excitation energies, equivalent to highly advanced solutions of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
186
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(187 citation statements)
references
References 22 publications
(26 reference statements)
1
186
0
Order By: Relevance
“…(17) requires a transformation into equations for real times, known as KB equations, which are then solved by time propagation. 16,20,21,52 From the knowledge of the Green's function any one-particle property of the system can be extracted. In particular, the time-dependent density can be obtained from the lesser Green's function as…”
Section: Many-body Technique: Kadanoff-baym Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…(17) requires a transformation into equations for real times, known as KB equations, which are then solved by time propagation. 16,20,21,52 From the knowledge of the Green's function any one-particle property of the system can be extracted. In particular, the time-dependent density can be obtained from the lesser Green's function as…”
Section: Many-body Technique: Kadanoff-baym Equationsmentioning
confidence: 99%
“…[15][16][17][18][19] In the MBPT, the many-body self-energy MB can be approximated by a selection of suitable Feynman diagrams, relevant for the description of the main scattering processes. In earlier work 31 we have found that the 2B approximation is in excellent agreement with accurate TD-DMRG results in the regime of weak to intermediate interaction strength for the Anderson impurity model.…”
Section: Many-body Technique: Kadanoff-baym Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nonequilibrium 2B has recently been applied to study atoms in laser fields. 44 On the contour, the 2B self-energy reads ͓with the effective interaction ͑30͔͒…”
Section: Nonequilibrium Second Born Approximationmentioning
confidence: 99%
“…It can also be used with many-body effects included through self-energy terms, in the Kadanoff-Baym/Keldysh equations for time-dependent and nonequilibrium problems. 37,38 The chief limitation is the use of localized basis functions and the approximation of Eq. ͑12͒.…”
Section: ͑50͒mentioning
confidence: 99%